Evaluation of microleakage for three types of light cure orthodontic band cement - Lara Riyadh Al-Banaa (Elsevier, 2022)
Objective: The aim of this study was to compare the microleakage of three types of light cure orthodontic band cement (Resilience, Band-it and Transbond Plus) and to compare low and high curing light intensities at the enamel-cement and band-cement interfaces in the gingival and occlusal margins. Materials and methods: Sixty extracted human premolars were divided into six groups (n = 10 specimens) according to the type of cement used and intensity of light cure. Microetched bands of upper premolars cemented to the teeth by Transbond Plus (3 M Unitek), Resilience (Orthotechnology) and Band-it (db Orthodontics). Three groups were cured by a standard mode light cure (over 900 mw/cm2) for 20 s, and the other three groups were cured with an extra mode light cure (over 2700 mw/cm2) for 6 s. The teeth were sealed by nail varnish and immersed for 24 h in 0.5% basic fuchsin solution. After that, the teeth were sectioned in the buccoligual direction, observed under a stereomicroscope, and then recorded for microleakage at the enamel-cement and band-cement interfaces in the gingival and occlusal margins. The statistical analysis was performed using Kruskal-Wallis and Mann-Whitney U tests, and the level of significance was set at P < 0.05. Result: The microleakage scores showed no significant differences at the enamel-cement and band-cement interfaces among the three types of orthodontic band cement subjected to low- and high-intensity curing light. Conclusions: The type of cement and intensity of light cure did not affect the amount of microleakage at either interface.